The availability of care among frail older adults: impacts on care management in a crisis context - the Fibra Study - Juliana Lustosa Torres; Lygia Paccini Lustosa (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2024)
Abstract Background: In Brazil, most of the care provided is informal, but its availability remains relatively little explored in the context of frailty. Objective: The objective of this study was to describe the availability of care among older adults from Belo Horizonte, Brazil, and its association with frailty. Method: This is a cross-sectional study based on 598 older adults from the Fibra-BH Study (2008/09). Frailty was defined using the 5-item of physical frailty phenotype. The availability of care included subjective and objective measures. Adjusting variables were age, sex, education, and self-rated health. Statistical analyses were based on a Poisson regression model with a robust error variance. Results: The prevalence of frailty was 11.4% and pre-frailty was 56.4%. The availability of care was slightly lower among frail than pre-frail and non-frail, where 17% lived alone, 14% had nobody to rely on, and 13% were childless. An association was observed between a lack of availability of care and frailty only among men, regarding living alone and having nobody to rely on. Conclusion: Only a small part of older adults have a lack of availability of care, but it is slightly higher among frail older adults. Focus on male older adults with a lack of availability of care is necessary due to a higher probability of having frailty or pre-frailty.